Pemilihan Alternatif Trase Kereta Api Di Kabupaten Bangkalan Menggunakan Metode Ahp - Astuti, Septiana Widi; Oka, AA. Bagus; Soimun, Ahmad (Politeknik Perkeretaapian Indonesia Madiun, 2019)
In the Dutch colonial era Madura has already used rail transportation. Initially, the railway transport is only used as a means transport of salt distribution, as the main commodity in Madura, between Kalianget and Kamal and vice versa. The Madura railroad has been completely closed since 1984 due to short distance operation which made the train is less competitive with other public transport. In 2009, because of the opening of the Suramadu bridge the growth of economical and social aspect in Madura especially Bangkalan began to grow. It is characterized by the development plan to build Central Business District (CBD) in the Sukolilo area and also build a container port in the area of ​​Tanjung Bulu Pandan that requires transportation infrastructure for distribution, such as train. The purpose of this research is to choose the best rail alignment in Bangkalan. The method used in this study used Analytical Hierarchy Process (AHP) which is a method of decision-making plan. This study provides two alternative, first alternative is reactivated existing trace as trace A that is existing trace linking Kamal to Bangkalan. While alternative 2 is build new railway line as trace B which began from tip of the Suramadu bridge to Tunjung. The results showed that building a new railway line was the chosen alternative with spatial criteria being the most important criteria that must take precedence in selecting alternative. Overall, building a new alignment from Suramadu to Bangkalan was considered more important by the respondents when viewed in terms of spatial planning, design, disaster vulnerability and funding needs.